Reprint of: Cytotoxicity, cell uptake and microscopic analysis of titanium dioxide and silver nanoparticles in vitro - Tomankova, Katerina; Horakova, Jana; Harvanova, Monika; Malina, Lukas; Soukupova, Jana; Hradilova, Sarka; Kejlova, Kristina; Malohlava, Jakub; Licman, Libor; Dvorakova, Marketa; Jirova, Dagmar; Kolarova, Hana (Food and chemical toxicology, 2015)
Commercially manufactured nanomaterials are used massively for modification of products of everyday use, including products intended for children. Therefore their potential risks have to be ultimately studied. Aside from toxicity of nanomaterials with known specific parameters, the end-consumer is potentially endangered by materials with unknown specification. Commercially available products are not usually accompanied by parameter/specification sheet providing the consumer with sufficient chemico-physical parameters allowing the evaluation of possible toxic effects. The aim of this work was to evaluate the declared parameters of commercially available TiO2 and Ag NPs employing chemico-physical methods and consequently in vitro cytotoxicity and genotoxicity tests performed on non-cancer cell lines. Based on the results of our complex study we can conclude that the data provided by the producers are not in good agreement with the performed measurements. Furthermore, all tested NPs penetrated into the SVK14 cells and all NPs had significant effect on the kinetics of ROS production in all cell lines (note: the ROS production has not been established as the major mechanism of cell damage elicited by Ag NPs). The study revealed greater cytotoxic potential of Ag NPs in comparison with TiO2 NPs and all of the studied NPs caused significant DNA damage.
Keywords: Silver nanoparticles; Titanium dioxide nanoparticles; In vitro cytotoxicity; Cell uptake; Raman spectroscopy